Strategic thinking a comprehensive guide - Betz, Frederick 1937- (Emerald Group Publishing Limited, 2016)
"By using actual histories of business successes and failures to illustrate theoretical concepts in strategic thinking, this book provides a fully comprehensive and practical view of the issues and current debates in leadership strategic thinking. Leadership and strategy are intricately connected--it is a crucial responsibility of any leader to formulate strategy, and in an organization, only the leader has the power to implement strategic change. Strategic thinking requires both idealism and realism--to imagine a better world, and to acquire the resources, skills and organization to get there. However, most organizations focus on short-term thinking for their employees and leave long-term strategy to the executives. But no high-level executive in any organization has full scope of operations--thus, for realistic strategy, there is a need for good top-down and bottom-up communication. When organizational communication is only top-down, high-level strategy can become only wishful thinking by the CEO."--Provided by publisher.